When n is a positive integer, what is the value of
n → ∞ lim ( − 1 ) n − 1 sin ( π n 2 + 0 . 5 n + 1 ) ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hi , in the very first line of your solution how did you write − 1 × ( − 1 ) n since you are introducing a -ve sign . Also ( − 1 ) n can't be -ve since it is not given if n is odd so even it can't be -ve
Nice solution
What's wrong with this:
First we note that sin ( π ( n 2 + 0 . 5 n + 1 ) 1 / 2 ) = sin ( π n ( 1 + ( 2 n ) − 1 + n − 2 ) 1 / 2 )
As a second observation ∣ ( − 1 ) n − 1 sin ( π n ( 1 + ( 2 n ) − 1 + n − 2 ) ) ∣ = ∣ sin ( π n ( 1 + ( 2 n ) − 1 + n − 2 ) ) ∣ ≤ 1 .
With this two observations in hand n → ∞ lim ∣ sin ( π n ( 1 + ( 2 n ) − 1 + n − 2 ) ) ∣ = ∣ n → ∞ lim sin ( π n ( 1 + ( 2 n ) − 1 + n − 2 ) ) ∣ Continuity = ∣ sin ( n → ∞ lim π n ( 1 + ( 2 n ) − 1 + n − 2 ) ) ∣ Continuity = ∣ sin ( n → ∞ lim π n × n → ∞ lim ( 1 + ( 2 n ) − 1 + n − 2 ) ) ∣ = ∣ sin ( n → ∞ lim π n ) ∣ = ∣ n → ∞ lim sin ( π n ) ∣ Continuity = 0 n is integer.
Log in to reply
Your mistake is in lim n → ∞ n ( 1 + ( 2 n ) − 1 + ⋯ ) = lim n → ∞ n × lim n → ∞ ( 1 + ( 2 n ) − 1 + ⋯ ) .
Also, you lost a factor 2 1 along the way when getting rid of the square root. It should become ( 4 n ) − 1 .
What was your motivation in writing sin in npi - theta form
A more concise solution (using that n is a positive integer): ( − 1 ) n − 1 sin ( π n 2 + 0 . 5 n + 1 ) = ( − 1 ) n − 1 sin ( π n 1 + 0 . 5 / n + 1 / n 2 ) = ( − 1 ) n − 1 sin ( π n ( 1 + 2 1 0 . 5 / n + O ( 1 / n 2 ) ) = ( − 1 ) n − 1 sin ( π n + π / 4 + O ( 1 / n ) ) = − sin ( π / 4 + O ( 1 / n ) ) → − sin ( π / 4 ) = − 2 1
What’s wrong with saying that sin ( π n 2 + 0 . 5 n + 1 ) → sin ( π n 2 ) = sin ( n π ) = 0 ?
yes exctly the same question as above, why cant I say, lim n → ∞ sin ( π n 1 + n 0 . 5 + n 2 1 ) = 0
Problem Loading...
Note Loading...
Set Loading...
n → ∞ lim − ( − 1 ) n ( − 1 ) n − 1 sin ( n π − π n 2 + 0 . 5 n + 1 )
n → ∞ lim − ( − 1 ) 2 n − 1 sin π ⎝ ⎜ ⎜ ⎛ n + n 2 + 2 n + 1 ( n − n 2 + 2 n + 1 ) ( n + n 2 + 2 n + 1 ) ⎠ ⎟ ⎟ ⎞
= n → ∞ lim − ( − 1 ) 2 n − 1 sin π ⎝ ⎜ ⎜ ⎜ ⎜ ⎛ n ( 1 + 1 + 2 n 1 + n 2 1 ) n 2 − n 2 − 2 n − 1 ⎠ ⎟ ⎟ ⎟ ⎟ ⎞
= n → ∞ lim − ( − 1 ) 2 n sin π ⎝ ⎜ ⎜ ⎛ 1 + 1 + 2 n 1 + n 2 1 2 1 + n 1 ⎠ ⎟ ⎟ ⎞
= − 1 × sin 4 π = − 2 1